A Relational Approach to Accounting Models. - Everest, Gordon C.; Weber, Ron (The Accounting Review, 1977)
ABSTRACT: This paper addresses some aspects of the problem of integrating accounting and information systems theories. Previous attempts at integration, especially the matrix and tree-theoretic approaches, are reviewed and evaluated. These attempts are criticized because they do not satisfy the requirements laid down by database management systems theorists as necessary for information systems to have long-term survival. The relational database management approach is introduced since it provides a means to fulfilling these requirements. To show its relevance to accounting, the relational approach is applied to a traditional managerial accounting model .and a traditional financial accounting model. Various data retrieval operations are shown on these models. Finally, future research directions of an integrative nature are identified.